Movimento de Educação de Base - MEB - No Estado da Paraíba: vestígios de uma experiência educacional (1966-1971) - Santos, Lidiane Nayara Nascimento dos (2017)
The Bases Education Movement – BEM – was created by the 50.370/1961 decree, having catholic and governmental stakes, investing in the Young and Adult Education with the layman contribution. The layman participation let the insertion of new ideologies at the movement, objecting the social awareness and transformation of the evolved public. This awareness unleashed the conservator elite dissatisfaction and starting by the civil-military blow of 1964, the most conservator devotes redrived the movement, getting new directions to the non-subversion of the established order. Was realized during the years, the movement had been using tactics to continue its social job. The BEM, since its creation, had acted by radiophone classes in the North, Northeast and Midwest regions, but some summaries point that at certain moment, it had used the direct alphabetization, without the radio, to contribute with the activities that had been already developed at the communities or at the areas where the radiophone waves didn’t come. Beyond this actuation, the movement devoted to the formation and refinement of groups that acted with de human development, principally, educationally. With these data, the movement studies were started, trying to find the vestiges presented by the BEM researchers about the existence of a radiophone school at Paraíba state, that was unviable. At this question, the views were directed to the history of this movement at the state, objecting to comprehend the BEM educational vestiges at Paraíba, between 1966 and 1970, considering the accessed documents. To analyze and comprehend these vestiges, the analysis presupposes of the “said and non-said” speech were used as support, that contributed to come better the sources vision and reading, as decrees, summaries, alphabetization projects, beyond the Paraíba archbishop letters, D. José Maria Pires and BEM representatives. Some Catholic Church documents were consulted, that oriented directly or indirectly the BEM discussions, as the encyclicals DivinisRedemptoris (1937), Mater et Magistra (1961),DiviniIlliusMagistri (1929), Gravissimumeducationis (1965) and Apostolicamactuositatem (1965). Beyond these sources, some actors that also researched the movement at others states were discussed: Fávero (2006); Râposo (1985), Wanderley (1984), Kolling (s/d), Kadt (2007), and others. So, was searched to collaborate with the rewriting of the BEM history at Paraíba, contributing to the education history at the state.